AGRIBUSINESS SYSTEM IN THE CONTEXT OF REFORM: PROACTIVE POLICY AND GLOBALIZATION OF FOOD SECURITY - Zhurynov G.M.,; Syzdykov B.Sh.,; Orazova B.B., (Academic Journal of Physical and Chemical Sciences, 2020)
In Kazakhstan, it is necessary to move from the system of stochastic theory of patching emerging gaps to the theory of sustainable development of agriculture with a gradual transition first to food independence for the main food products produced, and then to comprehensive food security. In the context of globalization, the problem of forming an effectively functioning food security system is very urgent for Kazakhstan. Sustainable development of domestic food production plays an important role in ensuring food security of the state. Raw materials for food production are products produced by agricultural producers, i.e. the agro-industrial complex of the country as a whole. It follows that the role of the country's agricultural sector in ensuring food security is very important. The material conditions of production underlying the formation and development of a single economic complex dictate both the opportunity and the need to improve methods of control and management of the economy in response to changing conditions and factors of production. They require a reorientation of enterprises, industrial associations and intermediate performance in the final results. Agro-industrial complex (AIC), as well as other cross-sectoral national economy, should effectively fulfill its operational requirements. The achievement of this goal contributes to functional and sectoral structure of the complex of production. The merit of the authorities, of course, should be to put what she conducts a proactive policy, not hidden, and builds defenses. To paraphrase a famous saying, we can say that the Kazakh government is preparing a sled in the autumn, so as not to have problems in the winter, and the current December proved faithful to these steps. In contrast to the many governments that have always played a waiting game, our calculates the situation a step further and build a policy based on domestic resources. Today, in a globalized world agricultural markets and mainstream food security of the country, agro-industrial complex of Kazakhstan has a tendency of stable growth of agricultural production. And this growth we have created all conditions. In order to ensure the sustainable development of agriculture, the development of national competitive advantage of domestic products on an ongoing basis to study foreign experience of agricultural development, the positive trends which can be adapted in the Republic of Kazakhstan.